ASSOCIATION OF VITAMIN D SERUM LEVELS AND OVARIAN CANCER : A SYSTEMATIC REVIEW - Supriyadi, Agung; Andimapali, Zulfikar; Fitria, Adina; Whisnu Dewanegara, Rahadiyan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Knowing the modifiable risk factors for prevention and improved prognosis is crucial, as the prognosis of ovarian cancer is poor and there are few population-level interventions for early identification and long-term therapeutic success. Research on cancer has shown a great deal of scientific interest in vitamin D since it may be one of these factors.Aims : This systematic review is to review the association of vitamin D serum levels in patients with ovarian cancerMethods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SCIENCE DIRECT, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 329 articles, whereas the results of our search on SCIENCE DIRECT brought up 298 articles. The results of the search conducted for the last year of 2014 yielded a total 8 articles for PubMed and 12 articles for SCIENCE DIRECT. In the end, we compiled a total of 4 papers, 3 of which came from PubMed and 1 of which came from SCIENCE DIRECT. We included four research that met the criteria.Conclusion: In summary, some of the studies showed vitamin D supplementation is not necessary to increase the survival rate of ovarian cancer in the absence of a vitamin D shortage. There are limited studies about the association of vitamin D and ovarian cancer.